Sepeda Motor Bodong Akibat Pajak Nunggak Dalam Perspektif Tafsir Hukum Ekonomi Syari’ah - Alghifari, Abuzar; Riskia, Isnaini; Hendriyadi, Hendriyadi (ASAS, 2022)
Through the law on traffic and road transportation number 22 of 2009, specifically article 74, the Government plans to delete vehicle data if the (PKB) is in arrears for up to two years. Based on the issue, the purpose of this study is to find out the views of the interpretation of Islamic economic law regarding bulging motorbikes due to tax arrears. Viewed the type of research, it is including library research where the main data is in the form of documentation of various information then they will be qualitatively analyzed using the content analysis method and the thematic interpretation method with the approach of sharia economic law theories. From the perspective of interpretation of shari'ah economic law, buying-selling as well as taxes are two completely different things. Legal buying and selling have the authority to guarantee full ownership of something. This is the reason why such conditional buying and selling are not legalized in Islam. Therefore, tax arrears cannot simply annul the ownership rights that have occurred from the sale and purchase contract. Thus, falsifying the status of a motorbike because of tax arrears is a wrong action. This case is similar to conditional buying and selling, a form of buying and selling that is prohibited in Islam. Keywords: Bulging, Motorcycles, Interpretation of sharia economic law